Penanganan Kerusakan Sungai Lusi Kabupaten Grobogan Jawa Tengah Akibat Banjir dan Erosi Pada Lereng Sungai: Penanganan Kerusakan Sungai Lusi Kabupaten Grobogan Jawa Tengah Akibat Banjir dan Erosi Pada Lereng Sungai - Andriawan, Aan; ANDRIAWAN, Aan Andriawan (Universitas Muhammadiyah Sorong, 2024)
ABSTRACT Jratunseluna river area is 9,576.01 km² wide crossing 10 regencies and 2 cities, one of which is Grobogan Regency. The River System in Jratunseluna river area consists of 4 systems: Semarang Barat, Dolok-Panggaron, Jragung-Tuntang, and Serang Lusi Juana (Seluna). There are 2 (two) main riversi in the Seluna River system: Lusi and Serang Rivers, both of which cross Blora, Grobogan, Kudus, and Demak Regencies. The research was conducted in Lusi Rivershed (DAS) in Klaten Hamlet, Ngaringan Village, Ngawen Sub District, Grobogan Regency. This research aims to find out physical condition of Lusi River, inundation height, total discharge, and inundation area on the existing cross-section of Lusi River and to find out safety factor in strengthening Lusi River slope. River gydrolic analysis was conducted based in direct procedure with software HEC-RAS version 5.0 help and the method used in the analysis was slope stability with Bishop’s wedge method. The result of field survey shows that river bank damage occurs in Lusi Rivershed due to flood, erosion, and condition of land proning to landslide in the riverbed. Meanwhile, the result of analysis using HEC RAS 5.0 with plan discharge Q 10 years shows inundatio heigh of 1.10 m, and total discharge/ total Q of 450.34 m³/s, and for the inundation area of 1478.35 m² and safety factor value in strengthening Lusi River slope using gabions in Klaten Village, Ngaringan, Wirosari, Grobogan, Central Java, the value of 1.2787 was found without gabions, 1.3115 with gabions, and 1.3800 for alternative gabion 3. Keywords: River, flood and landslide managemen